2018
DOI: 10.3390/ijms19092835
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling in Lung Cancer: From Oncogenesis to Cancer Treatment Resistance

Abstract: Hedgehog signaling pathway is physiologically activated during embryogenesis, especially in lung development. It is also reactivated in many solid tumors. In lung cancer, Hedgehog pathway is closely associated with cancer stem cells (CSCs). Recent works have shown that CSCs produced a full-length Sonic Hedgehog (Shh) protein, with paracrine activity and induction of tumor development. Hedgehog pathway is also involved in tumor drug resistance in lung cancer, as cytotoxic chemotherapy, radiotherapy, and targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 162 publications
(198 reference statements)
2
84
0
Order By: Relevance
“…The non-canonical cascade exists to elicit various cellular responses, especially in cancers [36]. One of the mechanisms of non-canonical SHH signaling involves the activation of Gli transcriptional factors independently of SHH, Ptch and SMO.…”
Section: Shh Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The non-canonical cascade exists to elicit various cellular responses, especially in cancers [36]. One of the mechanisms of non-canonical SHH signaling involves the activation of Gli transcriptional factors independently of SHH, Ptch and SMO.…”
Section: Shh Signaling Pathwaymentioning
confidence: 99%
“…Beside its critical role in multiple developmental processes of organs and tissues, such as bone (see above), the Hedgehog-Gli signaling pathway is aberrantly activated in several human cancers [35,36,[114][115][116][117][118].…”
Section: Shh Signaling In Os Et Esmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Giroux‐Leprieur et al . reported about the association of cancer stemness and drug resistance in terms of Hedgehog signaling, there are few previous reports about the correlation of cancer stemness and histological transformation.…”
mentioning
confidence: 99%
“…In this case we focus on the cancer stemness as the mechanisms of TKI resistance, because in our previous study we demonstrated the drug-tolerant clones were consisted of cancer stem cells and senescent cells. 4 Although Giroux-Leprieur et al reported about the association of cancer stemness and drug resistance in terms of Hedgehog signaling, 5 there are few previous reports about the correlation of cancer stemness and histological transformation.…”
mentioning
confidence: 99%